Conditional cooperation among the poor: a new profile? - Jonathan Gheyssens; Isabel Günther (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2013)
On the basis of a conditional contribution experiment conducted in Benin and Uganda, we argue that a conditional u-shaped profile exists, at least in poor communities. Under this profile, individuals invest considerably in public goods when nobody else does, reduce their commitment in reaction to positive group participation and turn into conditional cooperators after a threshold of others' participation is reached. For the understanding of the dynamics of repeated cooperation the implications of this group of u-shaped cooperators might be important.
Keywords: 330; Conditional cooperation; Public goods; Experiments; sub-Saharan Africa